WANITA KARIER DAN PEMBINAAN GENERASI MUDA - Ahdar Djamaluddin (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2018)
This article examines the effectiveness of career women in fostering young generation families. When he becomes a career woman, he considers that household harmony will not be realized especially in guiding his children especially to the people of Watansoppeng. The study found that career women in Watansoppeng played an active role in coaching young people through formal education by choosing the right school, intense communication with teachers and participation with children's social activities in school and through informal education such as sharing roles with husbands, being role models and application of discipline to family members. Increasing the role of career women in fostering the younger generation through formal and informal education in Watansoppeng through approaches to career women themselves, to husbands as heads of families, approaches to children approach to pengutan function and finally approaches through problem solving and approaches through religion and local culture.